Information leakage detection and protection of leaked information by using the MAC-IP binding technique - Koti, B. Raja; Kumar, G.V.S. Raj (International Journal of Engineering and Technology, 2018)
The Digital world is advancing in terms of technological development day by day, resulting in an instantaneous rise in Data. This massive amount of Data has introduced the thought of Big Data, which has attracted both the business and IT sectors leaving the scope for huge opportunities. In turn, securing this massive data has become a challenging issue in the field of Information and Communication Technology. In this paper, we have carried out the work on business information sharing data which contains some sensitive information to investigate the security challenges of data in the field of business communication. The article an attempt is also made to identify the user’s intention or behavior during the navigation of data. The greatest challenge that is associated here is to prevent the integrity of the data while sharing the data from organization to the third party, where there exist huge chances of data loss, leakages or alteration. This paper highlights the concepts of data leakage, the techniques to detect the data leakage and the process of protecting the leaked data based on encrypted form.